Homer Simpson Ponders Politics : Popular Culture as Political Theory - Dale, Timothy M.; Foy, Joseph J. (Book collections on Project MUSE., 2013)
It is often said that the poet Homer "educated" ancient Greece. In this book, the authors have assembled a team of notable scholars who argue, quite persuasively, that Homer Simpson and his ilk are educating America and offering insights into the social order and the human condition. Following Homer Simpson Goes to Washington (winner of the John G. Cawelti Award for Best Textbook or Primer on American and Popular Culture) and Homer Simpson Marches on Washington, this volume reveals how books like J.R.R. Tolkien's The Hobbit and J.K. Rowling's Harry Potter, movies like Avatar and Star Wars, and television shows like The Office and Firefly define Americans' perceptions of society. The authors expand the discussion to explore the ways in which political theories play out in popular culture.